Modeling Multiple Packet Filter With FSA For Filtering Malicious Packet - Kakkad Kruti, M; Vaghela, Krunal (International Journal of Computer Sciences and Engineering, 2015)
In this paper we are trying to explain about firewall. Firewall is required to secure your valuable information. As there are many ways to deal with network security, we are trying to use FSA for providing a security because it is powerful enough to express any possible stateless packet filter and also provide optimal result in case of multiple packet filter combined together. As filtering is somewhat difficult with stateless packets we are trying to solve some issues related to stateless packet filter.